Four-point amplitude from open superstring field theory - Berkovits, N.; Echevarria, C. T. (Elsevier B.V., 2000)
An open superstring field theory action has been proposed which does not suffer from contact term divergences. In this paper, we compute the on-shell four-point tree amplitude fi om this action using the Giddings map. After including contributions from the quartic term in the action, the resulting amplitude agrees with the first-quantized prescription. (C) 2000 Elsevier B.V. B.V. All rights reserved.